Kyrgyz Republic : Request for an 18-Month Arrangement Under the Exogenous Shocks Facility-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Kyrgyz Republic. (IMF Staff Country Reports; Country Report ;, 2008)
The Kyrgyz Republic's request for an 18-month Arrangement under the Exogenous Shocks Facility is discussed. International commodity prices continued to rise through much of 2008, resulting in a surge in inflation to more than 30 percent by mid-year and a widening of the current account deficit. A major shortfall in domestic hydropower capacity owing to low water levels is causing power shortages and necessitates the import of larger volumes of fuel and electricity, increasing the current account deficit further.